Lagdelt indholdsstruktur i selvstændige ytringer og direkte og indirekte ytringsgengivelse - Sørensen, Marie-Louise Lind; Boye, Kasper (Ny forskning i grammatik, 2017)
Based in Danish Functionel Linguistics, this article presents a unified analysis of semantic similarities and differences between i) the Danish main-clause types declarative, interrogative and imperative, which are argued to code resp. assertions, polar questions and directive speech acts, and ii) independent main clauses and the two types of clauses – dependent main clauses and complement clauses – which are used to report utterances directly and indirectly, respectively. It is argued i) that independent main clauses possess the layers illocutionary neustic, illocutionary tropic, state-of-affairs, and – in the case of declaratives and interrogatives – proposition, ii) that dependent main clauses lack an illocutionary neustic, and iii) that complement clauses in addition lack an illocutionary tropic.